Artemisinin biosynthesis and its regulatory enzymes: Progress and perspective - Wen, Wei; Yu, Rongmin (Pharmacognosy Reviews, 2011)
Artemisinin is an endoperoxidized sesquiterpene from the Chinese medicinal plant Artemisia annua, used as an effective anti-malarial drug. Its biosynthesis pathway has been investigated for many years for scientific interest and for potential manufacturing applications to fulfill the market demand. A number of regulatory enzymes of its biosynthesis process, including amorpha-4,11-diene synthase, CYP71AV1 and cytochrome P450 reductase, have been obtained and utilized to increase the content of artemisinin. However, a large knowledge gap still exists, and certain points of controversy have stirred debates within the field. In this review, the progress and perspective of artemisinin biosynthesis and its regulating enzymes are described.
Keywords: Artemisinin; biosynthesis pathway; progress and perspective; regulatory enzymes